Olaraga Antar Perguruan Tinggi - Nomi Kristina Tampilang; Melky Pangemanan (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Sports are one of the important aspects in student life, not only as a means to maintain physical health, but also as a medium to build character, cooperation, and competitive spirit. In Indonesia, inter-university sports activities are one of the effective means to improve sports achievements and strengthen relationships between students from various backgrounds. This activity not only focuses on the competitive aspect, but also on the formation of solidarity and friendship between students.